2018
DOI: 10.4103/ajns.ajns_98_17
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal shuntscope-guided ventricular catheter placement: Early experience

Abstract: Background:Placement of ventricular catheter (VC) in an optimal position is the most important factor in determining the outcome of shunt surgery. VC obstruction due to shunt tube placement in brain parenchyma, across the septa, tangled in the choroid plexuses and clogging of VC due to brain matter or other debris are common reasons resulting in shunt complete or partial dysfunction. To resolve these hurdles, many technical advancements have been made including navigation, stereotaxy, sonography, and ventricul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Endoscopy-assisted placement of intraventricular catheters using an endoluminal endoscope was reported in various modifications, allowing even for the placement of preassembled catheter-reservoir systems. [17][18][19] Although this technique has been demonstrated to allow for the precise placement of intraventricular catheters, its application is limited to a single purpose. In circumstances of decreased visibility secondary to bleeding, high protein contents or tissue debris, constant irrigation, and even active suctioning might be necessary, limiting the use of endoluminal endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopy-assisted placement of intraventricular catheters using an endoluminal endoscope was reported in various modifications, allowing even for the placement of preassembled catheter-reservoir systems. [17][18][19] Although this technique has been demonstrated to allow for the precise placement of intraventricular catheters, its application is limited to a single purpose. In circumstances of decreased visibility secondary to bleeding, high protein contents or tissue debris, constant irrigation, and even active suctioning might be necessary, limiting the use of endoluminal endoscopy.…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of advances in improving valve design and prevention of infection, the failure rate by the placement of a ventricular catheter during the shunting procedure has not been changed. The shunt failure in the first year after placement reported in the literature varies from 20 to 50% [ 14 , 19 22 ]. Catheter obstruction due to in-grow of the choroid plexus and occlusion of the proximal catheter lumen is estimated as one of the causes leading to shunting dysfunction [ 1 , 7 , 17 , 22 , 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison to our results, we had a proper placement in 90% in SG group compared to 65% in FH group. Several studies reported good success rates, especially with difficult ventricular configurations 20,22,23,26,27 . However, these studies did not include a control group.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…This allows the tip of the VC to be placed in the cerebrospinal fluid (CSF) system under visual control while avoiding touching the ventricular wall or the plexus. In addition, many authors recommend the use of a narrow or wide endoscope tube in difficult ventricular anatomy, where other methods cannot achieve an optimal position [20][21][22][23][24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%